Hosea-Micah - Goldingay, John (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2021)
"A highly regarded Old Testament scholar offers a substantive and useful commentary on Hosea-Micah and explores the contemporary significance of these prophetic books"--
Includes bibliographical references (pages 493-514) and indexes.
Keywords: Bible. -- Commentaries